Synthesis of imidazolium-based poly(ionic liquids) with diverse substituents and their applications in dispersive solid-phase extraction - Mohamed, Ahmad Husaini; Noorhisham, Nur Athirah; Bakar, Kamariah; Yahaya, Noorfatimah; Mohamad, Sharifah; Kamaruzaman, Sazlinda; Osman, Hasnah (Elsevier, 2022)
Imidazolium-based poly(ionic liquids) (PILs) belong to a subclass of polyelectrolytes characterised by a combination of a series of intrinsic ionic liquids features, spatial controllability, and polymeric architecture stability. Over the past few years, imidazolium-based PILs have attracted considerable attention in dispersive solid-phase extraction (DSPE) and the advances in its dynamic variances. The quest for new, simple, and improved dispersive adsorbent materials has focused on imidazolium-based PILs, which are versatile due to their wide range of chemical platform functionalities, selectivity, and efficiency. Recently, facile designs with various substituents during the synthesis of imidazolium-based PILs have led to an important development of new adsorbent materials for DSPE based techniques. The review aimed to provide perspective on the impact of various types and positions of substituents concerning novel preparation strategies of imidazolium based PILs. Moreover, the properties of imidazolium-based PILs adsorbents, their general synthesis approaches, performance in DSPE and its dynamic advance variances, and the challenges, issues, and advantages were thoroughly discussed. Imidazolium-based PILs are undoubtedly a competitor as dispersive adsorbent materials for DSPE based techniques.